1983
DOI: 10.1016/0035-9203(83)90128-1
|View full text |Cite
|
Sign up to set email alerts
|

Excreta disposal facilities and intestinal parasitism in urban Africa: preliminary studies in Botswana, Ghana and Zambia

Abstract: The relationships between intestinal parasitism and excreta disposal technologies in Gaborone (Botswana), Ndola (Zambia) and Kumasi (Ghana) were investigated. Parasitic prevalence and intensity rates amongst groups of urban residents having similar socio-economic status and housing, but different excreta disposal technologies, were compared. In Gaborone, there was no evidence of a difference in intestinal parasitism between those using aqua privies and having access to public taps and those in identical houses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 2 publications
0
12
2
1
Order By: Relevance
“…It seemed that sanitary/environmental conditions remain basic in Mataram, Lombok island, Indonesia. Some people still use the fingers when eating (Cairncross et al, 1997), consume well, pond or river water (Cairncross et al, 1997;Mckeown et al, 1999 ) and use privy/latrine type toilet (Feachem et al, 1983). Prevalence of hepatitis A, for instance, a typical waterborne infectious disease, is very high at no less than 90%, and the infection rates did not differ between the two areas (Brown et al, 1985;Hoang et al, 2008) Effects of pre-or co-infection of other organisms, including dengue, should be taken into account because the altered immune system may modify sensitivity or resistance to infection by H. pylori (Nurgalieva et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It seemed that sanitary/environmental conditions remain basic in Mataram, Lombok island, Indonesia. Some people still use the fingers when eating (Cairncross et al, 1997), consume well, pond or river water (Cairncross et al, 1997;Mckeown et al, 1999 ) and use privy/latrine type toilet (Feachem et al, 1983). Prevalence of hepatitis A, for instance, a typical waterborne infectious disease, is very high at no less than 90%, and the infection rates did not differ between the two areas (Brown et al, 1985;Hoang et al, 2008) Effects of pre-or co-infection of other organisms, including dengue, should be taken into account because the altered immune system may modify sensitivity or resistance to infection by H. pylori (Nurgalieva et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Even though, it is argued that in highly contaminated environments, faecal transmission in defecation ground may not be a single most important site for geohelminth infection (Feachem et al 1983), it was found to be a significant univariate risk factor for infection with intestinal helminthiasis, where in a high prevalence was seen in children defecating in open fields, compared to low prevalence among children who defecate in modern septic latrines. In Shopian district children are at particular risk with nearly 70 % of children less than the age of 15 years, defecating outdoors in either the open latrines or nearby fields.…”
Section: Discussionmentioning
confidence: 99%
“…Ascariasis occurs through ingestion of food and or water contaminated with faeces containing Ascaris eggs. Its transmission and distribution is largely determined by inadequate sanitary practices and improper faeces disposal 8,25,59 . The absence could be due to the fact that adult worms of Ascaris are regularly found in stool of infected individuals who then self-medicate with antihelmentics 12 after seeing these worms in their stool, in addition to improvement in prevailing social environment and behaviours of people in the communities 60,61 .…”
Section: Fig 3: Pictures Of Hookworm Larvae Recovered From the Stoolmentioning
confidence: 99%
“…There are about 20 major helminth infections of humans, affecting more than one third of the world's population 2 and the most common ones that account for most of the global helminth disease burden in many sub-Saharan African countries including Ghana are ascariasis, trichuriasis, strongyloidiasis, taeniasis, schistosomiasis and hookworm infections [3][4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%